Valorization of biodiesel side stream waste glycerol for rhamnolipids production by Pseudomonas aeruginosa RS6 - Baskaran, Shobanah Menon; Zakaria, Mohd Rafein; Ahmad Sabri, Ahmad Syafiq Mukhlis; Mohamed, Mohd Shamzi; Wasoh, Helmi; Toshinari, Maeda; Hassan, Mohd Ali; M. Banat, Ibrahim (Elsevier, 2021)
Biodiesel side stream waste glycerol was identified as a cheap carbon source for rhamnolipids (RLs) production which at the same time could improve the management of waste. The present study aimed to produce RLs by using Pseudomonas aeruginosa RS6 utilizing waste glycerol as a substrate and to evaluate their physico-chemicals properties. Fermentation conditions such as temperature, initial medium pH, waste glycerol concentration, nitrogen sources and concentrations resulted in different compositions of the mono- and di-RLs produced. The maximum RLs production of 2.73 g/L was obtained when P. aeruginosa RS6 was grown in a basal salt medium supplemented with 1% waste glycerol and 0.2 M sodium nitrate at 35 °C and pH 6.5. At optimal fermentation conditions, the emulsification index (E24) values of cooking oil, diesel oil, benzene, olive oil, petroleum, and kerosene were all above E24=50%. The surface tension reduction obtained from 72.13 mN/m to 29.4–30.4 mN/m was better than the surface activity of some chemical-based surfactants. The RLs produced possessed antimicrobial activities against Gram-negative and Gram-positive bacteria with values ranging from 37% to 77% of growth inhibition when 1 mg/mL of RLs was used. Concentrations of RLs below 1500 μg/mL did not induce phytotoxicity effects on the tested seeds (Vigna radiata) compared to the chemical-based- surfactant, SDS. Furthermore, RLs tested on zebrafish (Danio rerio) embryos only exhibited low acute toxicity with an LC50 value of 72.97 μg/mL at 48 h of exposure suggesting a green and eco-biochemical worthy of future applications to replace chemical-based surfactants.